Analisis Yuridis Pemberian Izin Poligami Karena Istri Tidak Memenuhi Kebutuhan Batin : Studi Putusan Pengadilan Agama Mataram Nomor 308/Pdt.G/2020/PA.Mtr - Ni Wayan Girisawitri; Diangsa Wagian (Private Law, 2022)
The purpose of this research is to study the reasons and requirement for polygamy consent according to the law, and to analyze the polygamy consent due to the wife’s incapability to meet the inner needs according the verdict number 308 /Pdt.G/ 2020 /PA. Mtr. This research is very beneficial to develop legal science or jurisprudence and it serves as a reference to similar research. This is a normative legal research. The data of this research is collected through a literature study. This research finds out that according the Article 4 paragraph (2) of The law No. 1 of 1974 concerning marriage, the polygamy can be approved only if: 1) wife is incapable to carry out her duties a wife; 2) wife have a disability; 3) wife has an incurable disease; and 4) wife can not give birth. This research also finds out that the judge's legal considerations in giving approval for polygamy refer to the provisions of Article 4 paragraph (2) alphabet (a), i.e. , the wife is incapable to carry out her duties a wife. In this verdict, judges have the opinion that the wife’s incapability to meet the inner needs of her husband is a form of the wife is incapable to carry out her duties a wife as stipulated inArticle 4 paragraph (2) of The law No. 1 of 1974 concerning marriage.